The Application of Maqasid-Oriented Approach in Islamic Bioethics: A Case Study on Fatwa Related to Cosmetic, Plastic and Reconstructive Surgery - Naqib Hamdan M; Mohd Anuar R; Aminudin H; Nur Najwa Hanani AR; Muhammad Faiz MS; Syamsul Azizul Marinsah (Kulliyyah of Medicine, International Islamic University Malaysia, 2021)
INTRODUCTION: Cosmetic surgery, which is a type of elective surgery designed to alter the physical features of the human body, is currently in high demand due to a combination of several main factors; namely low self-esteem, the desire to achieve beauty standards set by society, and the ubiquity of mass media and social media influencers. As a Muslim, cosmetic surgery must be evaluated from a jurisprudential lens to determine the level of necessity of the procedure, whether it reached the stage of essential (darurah), or necessity (hajah), or complimentary (tahsinah), along with close inspection of the maslahah B dan mafsadah involved with the aspect of maslahahdan mafsadahin need of further clarification. A close inspection of medical fatwas relating to cosmetic surgery reveals that procedures that are intended solely for physical beautification with no medical justification whatsoever are forbidden. MATERIALS AND METHODS: This study collect data from fatwas issued by seven fatwa institutions worldwide, will look into the application of maqasid al-shariʿain determining the legal status of cosmetic surgery in Islam. The data was analyzed thematically. RESULT: The findings from this study suggest that all fatwas pertaining to cosmetic surgery were decided based on the considerations of maqasid al-shariʿa, which will greatly aid doctors and patients in evaluating the need, or the lack thereof, to proceed with cosmetic surgery. CONCLUSION: The discussion of Islamic law or fatwa related to medicine requires synergy between sharia experts and medical doctors.